KONSEP PENGELOLAAN SAMPAH DI KAWASAN INDUSTRI - Shochib, Rosita (Jurnal Rekayasa Lingkungan)
Industrial parks play a signifi cant role in the production and use of goods and services. The proper management of solid waste is a major challenge for industrial parks due to the large quantity of wastes and the variability of waste characteristics from these types of developments. Therefore, integrated solid waste management has become very crucial to the industrial park managers. Such an approach requires industrial park managers to assess the overall use of resources, and to seek waste reduction, reuse and recycling opportunities both at the individual company level and among different tenant companies. The adoption of this method can bring both economic and environmental benefits.Key words : SWM, Industrial Park, 3R